Endometriosis of the vesico-vaginal septum: a rare and unusual localization (case report) - Yassir Ait Benkaddour; Affaf El Farji; Abderraouf Soummani (BMC, 2020)
Abstract Background We report a rare and unusual case of endometriosis in the vesico-vaginal septum. The location of this disease at this site is so uncommon that the literature about is very rare. Case presentation A 41-year-old female was presented with urinary symptoms. There was history of caesarean section. Physical examination revealed an anterior vaginal wall mass. Pelvic MRI showed an inter vesico-vaginal mass, suggesting a leiomyoma. Surgical excision was performed by the vaginal route. There were no postoperative complications. Histopathology examination showed focal endometriosis. Conclusion Endometriosis of the anterior compartment remains relatively rare; its localization to the vesico-vaginal septum (VVS) is very rare. With the occurrence of nonspecific cyclic urinary signs in women during periods of genital activity, endometriosis should be mentioned, especially in the presence of an antecedent of pelvic surgery.